2011
DOI: 10.1021/ol203161u
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Tirandamycin C

Abstract: Tirandamycin C is a newly isolated member of the tetramic acid family natural products. We described herein the first enantioselective synthesis of natural (−)-tirandamycin C, the postulated biosynthetic precursor of other members of this family. The highly stereoselective (>15:1) mismatched double asymmetric γ-stannylcrotylboration reaction of aldehyde 8 with crotylborane reagent (R)-E-9 was utilized to access the key anti, anti-stereotriad 18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Numerous synthetic pathways were used for the synthesis of 1-aminotetralins, including Friedel-Crafts acylations followed by reductive amination, [10] Diels-Alder reactions [11] or addition of a lithium anion to an imine. [12] More direct routes were also reported by Sutherland, via an elegant multi-bond forming domino strategy [13] and Masson, using a chiral phosphoric acid-catalyzed cyclization between anilines and phenylacetaldehydes. [14] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 We took advantage of this unexpected synthetic route to 1-aminotetralins by replacing the tryptamine 1 a by numerous secondary amines, enabling the development of a general method for the synthesis of tricyclic 1-aminotetralins 5 or 6 (Scheme 1, eq.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Numerous synthetic pathways were used for the synthesis of 1-aminotetralins, including Friedel-Crafts acylations followed by reductive amination, [10] Diels-Alder reactions [11] or addition of a lithium anion to an imine. [12] More direct routes were also reported by Sutherland, via an elegant multi-bond forming domino strategy [13] and Masson, using a chiral phosphoric acid-catalyzed cyclization between anilines and phenylacetaldehydes. [14] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 We took advantage of this unexpected synthetic route to 1-aminotetralins by replacing the tryptamine 1 a by numerous secondary amines, enabling the development of a general method for the synthesis of tricyclic 1-aminotetralins 5 or 6 (Scheme 1, eq.…”
mentioning
confidence: 85%
“…These new conditions allowed the chemoselective formation of 4 a, observed as the sole compound isolated in 66% yield (entry 7). The use of other allenaldehydes bearing fluorine or trifluoromethyl groups similarly led to the corresponding 1-aminotetralins 4 c-f with full chemoselectivities (entries [8][9][10][11].We next introduced a methoxy group on the indole ring and observed that this induced a decrease in the chemoselectivity, leading in all cases to the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 tetralins 4 g-i as the major products, in ratios close to 90/10 ( Table 1, entries [12][13][14].…”
mentioning
confidence: 91%
“…For example, Roush and co‐workers generated enantioenriched ( S )‐( E )‐γ‐substituted α‐stannyl allylic boranes from allenylstannane, and synthesized ( E )‐δ‐stannyl‐substituted anti ‐homoallylic alcohols with high enantioselectivity (Figure a) . This strategy was successfully applied to the asymmetric total syntheses of (−)‐tirandamycin C and (+)‐crocacin C . Enantioenriched ( S )‐( E )‐γ‐substituted α‐silyl allylic boranes are also feasible starting from allenylsilane .…”
Section: Figurementioning
confidence: 99%
“…Obviously, the racemic tetramic acid fragment 33 could be easily accessed by subjecting phosphonate 31 to glycine methyl ester to provide the amide 32 that further proceeded with a typical Lacey-Dieckmann cyclization and a DMB protection (Schlessinger et al had prepared similar tetramic acid core via the same method in his synthesis of tirandamycin A; see [48]) [49]. In contrast, the bicyclic ketal fragment 36 asks for precautious design to achieve the desired stereochemistry presented in tirandamycin C [25,48,[50][51][52][53][54][55][56]. The starting homoallylic alcohol 34, prepared from the mismatched double asymmetric stannylcrotylboration of an aldehyde, was treated with excess MeLi at low temperature to trigger the formation of the lactol intermediate C.…”
Section: C3-multienoyl Ta (Tirandamycin and Streptolydigin)mentioning
confidence: 99%